(untitled) (Research, Society and Development, 2021)
Lamiaceae is a family of vegetable species characterized by their medicinal applications, which include plants of the Eplingiella fruticosa species (Salzm. Ex Benth. Harley & J.F.B. Pastore). This species is exploited based on extractivism; thus, genetic erosion is a potential risk, and studies focused on strategies for conservation, domestication, and breeding of this species are essential. The objective of this work was to identify interactions in the environment that may predict growth and development of this species based on ecogeographic studies. Data of soil, climate, topography, geomorphology, phytogeography, and biome were collected at naturally occurring sites in the central-north, northeast, and metropolitan regions of Salvador, state of Bahia, and in the eastern and rural mesoregions of the state of Sergipe, Brazil. Data were collected in situ and at specialized sites of the Brazilian Institute of Geography and Statistics (IBGE), Brazilian National Institute of Space Research (INPE), Brazilian National Institute of Meteorology (INMET), and Brazilian Agricultural Research Corporation (EMBRAPA) and subjected to statistical analysis (Principal Component Analysis). The growth environment of E. fruticosa plants was typified as low-fertility sandy soils with high concentration and contents of aluminum (Al+3), within the domains of the Caatinga and Atlantic Forest biomes and Agreste region in the states of Bahia and Sergipe, with adaptation to a wide range of variation in temperature, rainfall depths, and altitude.